Effects of Landscape Fragmentation on Soil Loss in the Cerrado Biome, Brazil - Camelo, Ana Paula; Sanches, Keila; Matricardi, Eraldo Aparecido Trondoli; Sano, Edson Eyji; Souza, Alvaro Nogueira de; Miguel, Eder Pereira (Environmental Management and Sustainable Development, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Soil loss stands as a critical global challenge, posing economic and environmental threats to soil and water conservation. This study aimed to assess the impact of landscape changes on soil loss in the Descoberto River basin, encompassing 62 watersheds in the Cerrado biome in central Brazil. We analysed a 32-year time series (1985-2017) of land use and land cover data based on geostatistical techniques and spatiotemporal weighted regression analysis. Principal component analysis condensed 16 landscape metrics into three factors: aggregation/diversity, dispersion/adjacency, and patchiness. The average annual total soil loss across all 62 analysed watersheds was estimated at 73.3 ± 78.2 (standard deviation) ton ha<sup style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">−1<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">. A significant positive correlation was observed between landscape fragmentation and soil erosion, indicating that, as fragmentation increases, soil losses also increase. Furthermore, our analysis revealed a decreasing trend in soil loss rates in recent years, primarily attributed to the recovery of native vegetation since no significant soil management practices were widely implemented in the study area during the study period.